Mixed-flow impeller characteristics in baffled mixing tank - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Husaini, Muhamad; Jameel, Ahmed Tariq (Trans Tech Publications, Switzerland, 2012)
In recent times, impellers have been designed and modified to combine unique hydrodynamic features to overcome redundancy during mixing. One of such impeller is the mixed-flow impeller which displays a unique combination of radial and axial flow. In this paper, the flow characteristic of a mixed-flow impeller is reported. The main focus is to compare the axial and radial characteristic of the velocity component using experimental and numerical study. The continuity and momentum equation were solved using the Reynold’s stress model (RSM). The field of view away from and below the impeller compared better with the numerical solution for the mean, radial and axial velocity component. Although the RSM was used at a higher computational cost, associated power number and energy of the impeller was also observed to be better predicted.